(untitled) (Tempo e Argumento, 2023)
The scope of this article is the Sanctuary of Fátima in the Serra Grande in the city of São Benedito in the state of Ceará. My aim is to think about the uses of the past in the construction of a political culture pilgrimage in the present, from the historical analysis of the documents, such as based on newsletters and virtual magazines published by the sanctuary. The Sanctuary of Fátima in the Serra Grande has become one of the most important centers of pilgrimage in the Brazilian Northeast. Coming from the initiative of the clergy and lay people from Ceará, the religious building was built over the first two decades of the 21st century and since then has stood out with the reception of large contingents of pilgrims. The narrative records produced by the sanctuary allow us to glimpse the actions of the clergy in the invention of the recent past, linking it to the mystique of the Portuguese apparitions, as well as highlighting the devotion of the laity and the narratives of miracles.